Inuit gender parity and why it was not accepted in the Nunavut legislature - Williamson, Laakkuluk (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractIn this article, the historical circumstances that led up to the 1997 non-binding plebiscite on gender parity in what was soon-to-be Nunavut are considered. Firstly, traditional gender egalitarianism and fluidity in Inuit culture are described and exemplified by the values instilled in language, naming system, gendered roles and sexuality. Then, the political circumstances around the establishment of Nunavut and the way gender is played out on a political level are taken into account. The barriers against women in the electoral system are analysed and the arguments made for and against creating gender parity are evaluated. The vote on gender parity and the reasons why gender parity was finally rejected are reflected on. In the second part, the manners in which various organisations outside of government interact in order to address gender issues are scrutinised. Political and artistic bodies that represent women within Nunavut are contrasted against an organisation that contains Inuit men's voices, but does not represent them. Paradoxically, Inuit men still garner far more representation in the Legislative Assembly of Nunavut while at the social level they suffer more than women who are themselves more economically stable. The article ends with a discussion on the future of gender issues in Nunavut including the views held amongst Inuit youth on the topic.